MASTERS OF THE BALAFON, 2001, 2002. by Hugo Zemp. Colour, DVD Series. Produced by Selenium Films, distributed by Educational Resources (www.der.org). - Carver, Mandy (International Library of African Music, 2010)
pages: 142-143
Keywords: African Music